(untitled) (Architecture Image Studies, 2020)
As choreographer of dance group Vloeistof, specialized in public space, I chose to publish a journal written by dancer Izah Hankammer during the master-workshop program Making Space in Tilburg 2017. Making Space is a collaboration of Fontys University of the Arts in Tilburg and Dans Brabant, an organization for dance and choreography in Brabant, which is the Southern province of the Netherlands. During a week the second year students of the Dance Academy are exploring the public space as a stage, guided by choreographers who are experienced in this matter. This journal allows us to understand the specific aspects that we, dancers of Vloeistof, deal with in the streets. In a tangible way, the journal takes you along to gives insight into how we physically engage in and study public space, the passersby, and our art form. It is not easy to compare our strategies with those of a traditional dance group. The context of public space has led us to an ongoing exploration, wherein the process is as important as the outcome. To understand our methods, I believe it is necessary to crawl into the skin of my dancer, Izah, and to look at the space through her eyes. This journal is written in a personal manner, allowing the reader to see which issues and dilemmas the dancer deals with by claiming the public space for her performance. I hope this journal can open up my work to a broader field and discourse. What are the similarities between our interventions with other disciplines like graffiti or street art? What do we address when entering the public space with art without permission or announcement? How do we deal with the unexpected? How do we create our own stage and canvas? What are the boundaries we conquer in our daily work?